BERKUMPUL DAN BERSATU LEWAT SANTAPAN: PENDIDIKAN MULTIKULTURAL MELALUI PESTA MAKAN BEDULANG - Safirah Wulandah; Tio Budi Hartono; Bunyamin Maftuh; Wilodati Wilodati (Jurnal Analisa Sosiologi, 2024)
This article discusses the tradition of "makan bedulang" in Belitung as a source for learning about multiculturalism in sociology. The aim of this research is to understand the diversity of Belitung society, the philosophical values of the tradition of makan bedulang, and how multicultural education can be taught through cultural traditions like makan bedulang in Belitung society. This research is descriptive in nature, and the objects of study are the tradition of makan bedulang, its philosophical values, and multicultural education. Data collection was conducted through library research, and data analysis was done by analyzing the values in the tradition of makan bedulang and using those values as a source for multicultural education. The results of this study indicate that: (1) the background of the Belitung island community is very diverse in terms of ethnicity, culture, and nationality; (2) the tradition of makan bedulang is a tradition that has many meaningful values, including ethics, aesthetics, religion, and social values; and (3) the tradition of makan bedulang can be used as a source for teaching multicultural education in the subject of sociology.